Introducing MySQL Shell administration made easy with Python - Bell, Charles (Apress, 2019)
Use MySQL Shell, the first modern and advanced client for connecting to and interacting with MySQL. It supports SQL, Python, and JavaScript. Thats right! You can write Python scripts and execute them within the shell interactively, or in batch mode. The level of automation available from Python combined with batch mode is especially helpful to those practicing DevOps methods in their database environments. Introducing MySQL Shell covers everything you need to know about MySQL Shell. You will learn how to use the shell for SQL, as well as the new application programming interfaces for working with a document store and even automating your management of MySQL servers using Python. The book includes a look at the supporting technologies and concepts such as JSON, schema-less documents, NoSQL, MySQL Replication, Group Replication, InnoDB Cluster, and more. MySQL Shell is the client that developers and database administrators have been waiting for. Far more powerful than the legacy client, MySQL Shell enables levels of automation that are useful not only for MySQL, but in the broader context of your career as well. Automate your work and build skills in one of the most in-demand languages. With MySQL Shell, you can do both! What You'll Learn: Use MySQL Shell with the newest features in MySQL 8 Discover what a Document Store is and how to manage it with MySQL Shell Configure Group Replication and InnoDB Cluster from MySQL Shell Understand the new MySQL Python application programming interfaces Write Python scripts for managing your data and the MySQL high availability features.